Q-switched and mode-locked thulium doped fiber lasers with nickel oxide film saturable absorber - Rusdi, Muhammad Farid Mohd; Rosol, Ahmad Haziq Aiman; Rahman, Mohd Fauzi Ab; Mahyuddin, Mohamad Badrol Hisyam; Latiff, Anas Abdul; Ahmad, Harith; Harun, Sulaiman Wadi; Yasin, Moh (Elsevier, 2019)
A passively Q-switched and mode-locked fiber laser based on thulium-doped fiber laser (TDFL) cavity was demonstrated utilizing nickel oxide (NiO) nanoparticles as a saturable absorber (SA). The NiO synthesis was carried out by using a facile sonochemical method and the prepared NiO thin film was sandwiched between two optical fiber ferrule connectors in the TDFL ring cavity. By controlling the loss and gain in the cavity, stable Q-switching operation was obtained. The repetition rate and pulse width were tunable from 6.71 kHz to 19.58 kHz and from 9.16 μs to 4.24 μs respectively, at different pump powers, ranging from 528 mW to 711 mW. The Q-switched TDFL was centered at 1900.52 nm and had maximum pulse energy and slope efficiency of 0.31 μJ and 2.58%, respectively. On the other hand, self-starting mode-locked TDFL was achieved by employing 10 m scandium-doped fiber into the ring cavity and remained stable within a pump power range of 821–967 mW. The TDFL mode-locked had a central wavelength of 1928.81 nm, at a threshold pump power of 821 mW. The repetition rate and pulse width were 8.10 MHz and 61.27 ns, respectively, while the slope efficiency was measured to be 2.20 %. © 2019